Distribution and Diversity of Herpetofauna in Upper River of Mount Sindoro, Central Java - Subeno Subeno (Jurnal Ilmu Kehutanan)
Most of area on the slopes of Mount Sindoro has been converted from forest area to other land-use types, particularly into agriculture area. The massive conversion in this region can have a significant effect for its biotic conditions. The exploration of fauna, especially herpetofauna, is highly necessary as they can be used as indicators of environmental degradation. The purpose of this study was to explore the distribution and diversity of herpetofauna in the upper river on the slopes of Mount Sindoro. The method used in this study was the Visual Encounter Survey (VES) with transects design. Transects were placed with the length of 1 km along rivers in the study area. We collected herpetofauna species, number of individuals, measured snout-vent length, weight, identified sex, and observing  their activities when encountered. Further, Shannon-Wiener diversity index was used to determine the diversity of herpetofauna. The mapping distribution of herpetofauna was done by processing the coordinates of an encountered herpetofauna with using ArcView 3.3. The results showed that from all of the study site, it had been found 14 species of herpetofauna which consisted of 4 species of reptiles and 10 species of amphibians. Family Ranidae and Dicroglossidae were dominant amphibians with 3 species. Further, family Bufonidae, Megophrydae, Microhylidae, and Rhacophoridae had 1 species for each. Four species of reptiles were found from 4 different families (Colubridae, Agamidae, Gekkonidae and Scincidae). Herpetofauna diversity index in the region had a value of 1.03 which was considered in a low category level. Distribution of herpetofauna species were varied i.e. 1 species scattered throughout the observation location whereas 2 species were spread across four observation sites. In addition, 1 species was spread over 3 locations, 3 species were spread across 2 locations and 6 species were only found in 1 location.